2011
DOI: 10.1007/s13580-011-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

An effect of light emitting diode (LED) irradiation treatment on the amplification of functional components of immature strawberry

Abstract: This study has been carried out aiming to have the materials for the use of selective control of specific functional component contents of vegetables and fruits by using LED light source in future through examination and analysis on the influence of LED light source (385 nm, 470 nm, 525 nm, and 630 nm) on the functional components and quality change of immature strawberry. Soluble solid content was 9.87% immediately after harvest and in 4 storage days, it gradually increased as 12.77% for the test group which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 8 publications
4
27
0
Order By: Relevance
“…The TPC increased with the storage time, of 148.9 and 127.8 mg GAE kg −1 for the red and green LED exposed bananas, respectively, on day 8, which were 27% and 9.2%, respectively, higher than that of the control group. These results agree with the studies that investigated the effect of different LED wavelengths on accumulation of phenolic compounds in postharvest strawberry, and cabbage …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The TPC increased with the storage time, of 148.9 and 127.8 mg GAE kg −1 for the red and green LED exposed bananas, respectively, on day 8, which were 27% and 9.2%, respectively, higher than that of the control group. These results agree with the studies that investigated the effect of different LED wavelengths on accumulation of phenolic compounds in postharvest strawberry, and cabbage …”
Section: Resultssupporting
confidence: 91%
“…Besides, green light may participate in reactions not directly exposed to the light stimulus, as it is efficiently transmitted through the plant tissues . Previous studies have also shown that green light treatments improved the sugar content of stored strawberries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in baby leaf lett uce, Li and Kubota (11) showed an increase in TPC aft er exposure to LED light from 600 to 700 nm. Using LED light at 470 nm, Kim et al (36) reported signifi cantly higher TPC in strawberry fruit, and as reported by Zhan et al (41), storage of broccoli under fl uorescent light increased TPC.…”
Section: Resultsmentioning
confidence: 63%
“…Effects on ascorbic acid levels were observed in lettuce (Li & Kubota ), strawberry (Kim et al . ), kale (Deng et al . ) and Chinese cabbage (Li et al .…”
Section: Nutrients and Neutraceuticalsmentioning
confidence: 99%